Resistance of a short-term memory concealed information test with famous faces to countermeasures. - Delmas, Hugues; Ciocan, Camélia; Novopashyna, Mariya; Paeye, Céline (Memory & Cognition, 2024)
The concealed information test (CIT) aims at identifying knowledge that a person wants to hide, by measuring physiological indices during the presentation of known versus unknown items. Recently, Lancry-Dayan et al. (Journal of Applied Research in Memory and Cognition, 7 (2), 291–302, 2018) proposed a new version of this test that included a short-term memory task to maximize differences between responses to items. Participants were asked to memorize four pictures of faces that included one face of an acquaintance. The authors observed that participants looked at the familiar face during the first second and then tended to avoid it. This specific orientation-avoidance pattern occurred even in participants instructed to conceal their familiarity with the known faces (in a spontaneous or a guided manner). In a first experiment, we reproduced Lancry-Dayan et al.'s (2018) study using photos of famous faces. The pattern found by Lancry-Dayan et al. was observed in participants asked to perform the memory task only, participants asked to conceal their familiarity with the famous faces, and participants of a countermeasure group. In a second experiment, we tested the robustness of Lancry-Dayan et al.'s countermeasure. We modified the instructions by emphasizing the oculomotor task or giving feedback. While between-group differences in gaze-pattern appeared after feedback was provided, classification analyses were still able to distinguish between familiar and unfamiliar faces accurately, which revealed the good resistance of this new CIT protocol to countermeasures.